Interactive Visual Learning Media to Enhance Students' Learning Outcomes in Islamic Religious Education on Peaceful Coexistence - Habib Muhaidhori; Imron Fauzi; Zaenul Hadi (LPTK UIN Syekh Wasil Kediri, 2025)
The low learning outcomes of students in the lesson “Living in Harmony Together” provided the context for this study. Conventional teaching methods tended to limit student engagement and made it difficult for students to understand the material. This classroom action research aims to improve students’ learning outcomes by implementing interactive visual media. The study involved 16 fifth-grade students and was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. Data were collected through observation, tests, and interviews. The results indicate consistent improvements in students’ learning outcomes. In the pre-cycle stage, the average score was 65.25, with classical mastery reaching only 43.75%. After the implementation of interactive visual media in Cycle 1, the average score increased to 75.25, and classical mastery reached 75%. Further improvement was observed in Cycle 2, with the average score increasing to 84.6, and all students met the Minimum Learning Mastery Criteria, achieving 100% classical mastery. In addition, students demonstrated greater engagement, cooperation, and tolerance throughout the learning process. These findings indicate that interactive visual media are effective in improving students’ learning outcomes on the topic “Living in Harmony Together.” In practice, this study suggests that teachers are encouraged to integrate diverse and creative interactive media to strengthen student engagement and optimize learning outcomes in similar learning contexts.